2009
DOI: 10.1002/app.29827
|View full text |Cite
|
Sign up to set email alerts
|

Effect of heterophasic or random PP copolymer on the compatibility mechanism between EVA and PP copolymers

Abstract: Compatibility mechanisms between EVA and PP copolymers (C-PP) blends have been studied as a function of the type of copolymer, using a heterophasic PP copolymer (PP-EP) and a random PP copolymer (PP-r-EP), with similar ethylene content. The morphology and thermal and mechanical properties of PP/EVA blends with different levels of EVA containing 28% vinyl acetate (VA) were determined. The obtained results indicated compatibility for both systems showing interactions at the amorphous interfaces; however, this in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…As the random content in the blend increases (H-20R), a decrease in the melting point is also observed. This is expected due to some typical characteristics of random copolymers, as their lower crystallinity and polymer architecture [27,32,33,34,35]. The analysis of experimental data (Table 3 and Table 4) and the SEM examinations revealed that membranes differing on blending ratio have an optimum value close to 10 percent for the random copolymer, and 20 percent for the heterophasic PP—where higher pore density and a pore distribution fairly homogeneous were achieved.…”
Section: Resultsmentioning
confidence: 92%
“…As the random content in the blend increases (H-20R), a decrease in the melting point is also observed. This is expected due to some typical characteristics of random copolymers, as their lower crystallinity and polymer architecture [27,32,33,34,35]. The analysis of experimental data (Table 3 and Table 4) and the SEM examinations revealed that membranes differing on blending ratio have an optimum value close to 10 percent for the random copolymer, and 20 percent for the heterophasic PP—where higher pore density and a pore distribution fairly homogeneous were achieved.…”
Section: Resultsmentioning
confidence: 92%
“…In a complex ternary system as PP‐EP/EVA/clay, it has been found that PP‐EP/EVA ratio is a determining factor in morphological, thermal and mechanical final composite properties; in this case 40/60 PP‐EP/EVA ratio was found to be the most adequate according to previous reports .…”
Section: Introductionmentioning
confidence: 74%
“…''PP copolymer", ''PPC", ''Hi-PP", ''co-PP" or ''PP copo" is a class of PP with improved impact properties. However, it is not always clear if it addresses a random copolymer of propylene and ethylene, a block copolymer, a blend, or an EPDM/EPR additived PP (Bouvard et al, 2016;Ramírez-Vargas et al, 2009;Roumeli et al, 2014;Zhou et al, 2008). Similarly to the case of HDPE and LDPE, PPH has supe-rior modulus and hardness but PPC is more processable and impact resistant.…”
Section: Propylene Based Polymers: Pp Homopolymer Pp Copolymer and Epdmmentioning
confidence: 99%